Peningkatan Kemampuan Bahasa Inggris Anak Melalui Metode Edukasi Kreatif di Rumah Baca Egad Kairos - Sherly Gaspersz; Christin Meirdhika Lekatompessy (CV. ITTC INDONESIA, 2025)
This study aims to analyse the effectiveness of creative education methods in improving children's basic English skills at Rumah Baca Egad Kairos, a non-formal learning space established by Putri Papua from Maybrat. The activities are conducted free of charge every Saturday and Sunday and target primary and secondary school children in the 3T region of West Papua. The creative educational methods employed include language games, songs, picture cards, and enjoyable, participatory small-group discussions. The study adopts a descriptive qualitative approach with simple quantitative elements (mixed method), as well as a Participatory Action Research (PAR) design across two cycles. Data was collected through participatory observation, pre-tests and post-tests, interviews, and activity documentation. The research results showed a significant improvement in children's vocabulary mastery and speaking confidence. The average pre-test and post-test scores increased from 47% to 70% (elementary school) and from 50% to 80% (junior high school). Additionally, the children demonstrated enthusiasm for learning, self-confidence, and active engagement in the learning process. The creative educational method proved effective in improving English language skills and can serve as a relevant contextual learning strategy for strengthening children's literacy in the 3T region community.